Postpartum diastasis of the pubic symphysis: case report and literature review - Uvarovas, Valentinas; Žukauskas, Povilas; Šiatkus, Tadas; Masionis, Povilas (Lietuvos chirurgija, 2015)
Postpartum diastasis of the pubic symphysis has the incidence from 1 in 300 to 1 in 30,000 deliveries. Under the action of progesterone and relaxin, a 1 cm widening of pubic symphysis is considered to be physiological and necessary for normal delivery. However, any higher widening is always pathological, involving the damage of pubic and sacroiliac ligaments. Multiparity has been identified as the only independent risk factor. Because this pathology often manifests as chronic pain in the pubic symphysis region, it is often mistakenly stated as a normal postpartum occurrence. It is only later when the symptoms of pelvic instability and pubic osteitis appear. Postpartum symphysiolysis is a clinical challenge to a physician due to low awareness and the postpartum period important to both the patient and the newborn.
Keywords: post partum; diastasis; symphysiolisis